1978
DOI: 10.1172/jci108957
|View full text |Cite
|
Sign up to set email alerts
|

Iodothyronine Metabolism in Rat Liver Homogenates

Abstract: A B S T R A C T To investigate mechanisms of extrathyroidal thyroid hormone metabolism, conversion of thyroxine (T4) to 3,5,3'-triiodothyronine (T3) and degradation of 3,3',5'-triiodothyronine (rT3) were studied in rat liver homogenates. Both reactions were enzymatic. For conversion of T4 to T3, the Km of T4 was 7.7 ,uM, and the Fasting resulted in inhibition of T4 to T3 conversion and of rT3 degradation by rat liver homogenates which was reversible after refeeding. Serum T4, T3, and thyrotropin concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
131
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(146 citation statements)
references
References 53 publications
12
131
2
Order By: Relevance
“…It is not yet clear how iron deficiency exerts its effects on deiodinase activity. Kaplan and Utiger have shown that outer ring deiodinase activity is not affected by either ferrous or ferric ions in an in vitro incubation method (Kaplan and Utiger, 1978). This, of course, does not rule out the possibility that iron needs to be incorporated into the enzyme during synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…It is not yet clear how iron deficiency exerts its effects on deiodinase activity. Kaplan and Utiger have shown that outer ring deiodinase activity is not affected by either ferrous or ferric ions in an in vitro incubation method (Kaplan and Utiger, 1978). This, of course, does not rule out the possibility that iron needs to be incorporated into the enzyme during synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…IOPA inhibits all three types of deiodenase enzymes. Although the effect of IOPA is strong on type II and III, it is comparatively weak on type I (Kaplan & Utiger 1978, St Germain 1994. At the end of this treatment, 15 hypothyroid rats were killed and the remaining 15 hypothyroid rats received daily injections for 2 weeks of 15 mg T 3 /100 g body weight (Sigma-Aldrich Corp.).…”
Section: Animals and T 3 Determinationmentioning
confidence: 99%
“…This may be because not enough samples were studied or that they were not collected at the exact postpartum time when the transient rise occurred. On the contrary, the frequent and precise sampling practiced by Davicco et al (1982) (Balsam and Ingbar, 1979 ;Kaplan and Utiger, 1978 ;Naito et al, 1981) and piglets (Slebodzinski et al, 1982), has been shown to result in a decrease of circulating T3 in these species (Chopra, 1980 ;Hastings and Zeman, 1979 ;Heinen et al, 1981 andSlebodzinski et al, 1982, respectively) ; this phenomenon has also been shown in humans (Azizi, 1978 ;Burman et al, 1979 ;Suda et al, 1978), adult sheep (Blum et al, 1980), growing bulls Tveit and Almlid, 1980), deer (Bahnak et al, 1981), chickens (May, 1978) …”
Section: Introductionmentioning
confidence: 99%